Online Education: Worldwide Status, Challenges, Trends, and Implications. Issue 4 (2nd October 2018) - Palvia, Shailendra; Aeron, Prageet; Gupta, Parul; Mahapatra, Diptiranjan; Parida, Ratri; Rosner, Rebecca; Sindhi, Sumita
ABSTRACT: Online education in its various modes has been growing steadily worldwide due to the confluence of new technologies, global adoption of the Internet, and intensifying demand for a workforce trained periodically for the ever-evolving digital economy. Online education is on track to become mainstream by 2025. This editorial documents country-level factors that impact quantity and quality of online education. Such factors include industry (business); governments at local, state, and federal levels; country laws; ICT capacity; Internet/mobile technology diffusion; and income and digital divide. We provide implications for country and world organizations concerning online education.